Inhibition of miR-101-3p prevents human aortic valve interstitial cell calcification through regulation of CDH11/SOX9 expression - Jianglei Chen; Yi Lin; Zhongjie Sun (BMC, 2023)
Abstract Background Calcific aortic valve disease (CAVD) is the second leading cause of adult heart diseases. The purpose of this study is to investigate whether miR-101-3p plays a role in the human aortic valve interstitial cells (HAVICs) calcification and the underlying mechanisms. Methods Small RNA deep sequencing and qPCR analysis were used to determine changes in microRNA expression in calcified human aortic valves. Results The data showed that miR-101-3p levels were increased in the calcified human aortic valves. Using cultured primary HAVICs, we demonstrated that the miR-101-3p mimic promoted calcification and upregulated the osteogenesis pathway, while anti-miR-101-3p inhibited osteogenic differentiation and prevented calcification in HAVICs treated with the osteogenic conditioned medium. Mechanistically, miR-101-3p directly targeted cadherin-11 (CDH11) and Sry-related high-mobility-group box 9 (SOX9), key factors in the regulation of chondrogenesis and osteogenesis. Both CDH11 and SOX9 expressions were downregulated in the calcified human HAVICs. Inhibition of miR-101-3p restored expression of CDH11, SOX9 and ASPN and prevented osteogenesis in HAVICs under the calcific condition. Conclusion miR-101-3p plays an important role in HAVIC calcification through regulation of CDH11/SOX9 expression. The finding is important as it reveals that miR-1013p may be a potential therapeutic target for calcific aortic valve disease.